2000
DOI: 10.1523/jneurosci.20-11-04030.2000
|View full text |Cite
|
Sign up to set email alerts
|

cAMP Response Element-Mediated Gene Transcription Is Upregulated by Chronic Antidepressant Treatment

Abstract: Regulation of gene transcription via the cAMP-mediated second messenger pathway has been implicated in the actions of antidepressant drugs, but studies to date have not demonstrated such an effect in vivo. To directly study the regulation of cAMP response element (CRE)-mediated gene transcription by antidepressants, transgenic mice with a CRE-LacZ reporter gene construct were administered one of three different classes of antidepressants: a norepinephrine selective reuptake inhibitor (desipramine), a serotonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
259
1
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(286 citation statements)
references
References 47 publications
19
259
1
7
Order By: Relevance
“…One piece of evidence of particular interest was discovered when we were studying the influence of antidepressants on CREB phosphorylation. We reported that antidepressant treatment increases the phosphorylation of CREB, measured with a phospho-specific antibody ( Figure 5) (Thome et al 2000). The additional point of interest in these studies was that under basal conditions there was prominent expression of phospho-CREB in cells within, or adjacent to, the subgranular zone where the progenitor cells are located (Figure 4).…”
Section: Role Of the Camp-creb Cascade In Adult Neurogenesismentioning
confidence: 94%
See 2 more Smart Citations
“…One piece of evidence of particular interest was discovered when we were studying the influence of antidepressants on CREB phosphorylation. We reported that antidepressant treatment increases the phosphorylation of CREB, measured with a phospho-specific antibody ( Figure 5) (Thome et al 2000). The additional point of interest in these studies was that under basal conditions there was prominent expression of phospho-CREB in cells within, or adjacent to, the subgranular zone where the progenitor cells are located (Figure 4).…”
Section: Role Of the Camp-creb Cascade In Adult Neurogenesismentioning
confidence: 94%
“…This has led to the discovery that repeated long-term antidepressant administration up-regulates the cAMP-CREB (cAMP response element binding protein) cascade and expression of brain derived neurotrophic factor (BDNF) in hippocampus ( Figure 2) (Nibuya et al 1995(Nibuya et al , 1996Thome et al 2000). Both CREB and BDNF are known to play a role in synaptic plasticity as well as neuronal survival (see Finkbeiner 2000;Duman et al 2000).…”
Section: Antidepressant Treatment Increases Adult Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…While the expression of CREB in the hippocampus of WT mice was enhanced by chronic administration of both desipramine and fluoxetine, CREB mRNA levels in the cortex were not significantly affected by either antidepressant drug. Support for a selective region-specific effect of antidepressants on CREB expression is provided by a study using post-mortem tissue from patients suffering from major depression that showed CREB expression to be enhanced in the temporal, but not occipital, cortex after treatment with antidepressants (Dowlatshahi et al 1998).One explanation for the different expression patterns of CREB displayed by the cortex and hippocampus may be the upregulation of two cAMP specific phosphodiesterase isoforms, PDE4A and PDE4B, that were upregulated in the cortex but not in the hippocampus of rats after chronic antidepressant treatment (Fujimaki et al 2000;Thome et al 2000). Phosphodiesterases play a crucial role in converting cAMP to 5Ј-AMP, and inhibit the transduction pathway leading to the activation of CREB.…”
mentioning
confidence: 99%
“…Levels of CREB and of CREB-mediated transcription are increased in the hippocampus and cerebral cortex by chronic antidepressant treatments, including ECS (Nibuya et al, 1996;Thome et al, 2000;Koch et al, 2002;Nakagawa et al, 2002). This upregulation of CREB may help restore normal cAMP signaling in these brain regions, whereas abnormally low levels of CREB in depressed patients have been reported (Dowlatshahi et al, 1998;D'Sa and Duman, 2002).…”
Section: Introductionmentioning
confidence: 99%